The Effect of Financial Performance on Stock Prices in Transportation Companies Listed on the IDX 2017-2021 Period - Nuranisa Al Azighah; Wa Ode Rayyani; Firman Syah (IECON: International Economics and Business Conference, 2023)
The purpose of this study was to examine the effect of financial performance as represented by four variables, namely: Current ratio, Return on Equity, Earning per Share, and Debt to Equity Ratio on stock prices. The population in this study are transportation companies listed on the Indonesia Stock Exchange for the 2017-2022 period. The sampling technique used purposive sampling technique. Based on predetermined criteria obtained a sample of 9 companies. The type of data used in this study is secondary data with multiple regression methods and using SPSS for windows. The results of this study indicate that the Current ratio has a negative and no significant effect on stock prices, Return on Equity has a positive and significant effect on stock prices, Earning per Share has a negative and no significant effect on stock prices, and the Debt to Equity Ratio has a negative and no significant effect on stock prices.